(untitled) (Journal of Oriental Studies, 2018)
This article provides a comparative analysis of methods of teaching phonetics of Chinese language by teachers from China and local teachers of the KazUIR & WL named after Ablai Khan, by the results of the analysis was made the conclusion about the advantages and disadvantages of teachers in teaching Chinese language.